2018
DOI: 10.1016/j.forpol.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation in the Welsh Woodlands: Community based forestry as collective third-sector engagement

Abstract: Commonly owned forests and common property regimes are types of forest ownership that exist in many European countries in various forms: they include traditional commons with a more or less unbroken history of 500 years or more, typically to be found in Austria, France, Italy, Romania, Slovenia, Spain and Switzerland (Živojinović et al., 2015). As an outcome of land reforms in the 18th and 19th centuries, community-owned or-managed forests were established for instance in Poland, Hungary, Slovakia and Sweden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…Within the reviewed studies, the involvement of the local community has been identified as a key factor for building legitimacy within the community and for being able to mobilise the necessary resources that support the emergence and the sustainability of these organisations (Healey, 2015;Jarl Borch et al, 2008;Valchovska and Watts, 2016;Vestrum, 2014;Vestrum et al, 2017). This local involvement also shows the critical role played by volunteers' time, energy and expertise, both in the emergence and sustainability of rural social enterprises (Calderwood and Davies, 2012;Farmer et al, 2008;Haugh, 2007;Ludvig et al, 2018;Perry and Alcock, 2010). Nevertheless, the presence of volunteers also carries downsides, as they can limit the growth potential of the organisations, create tension with paid staff and an excessive reliance on them can provoke volunteer fatigue and burn-out (Calderwood, 2013;Sonnino and Griggs-Trevarthen, 2013;Wyper et al, 2016).…”
Section: Social Enterprises In Rural Areasmentioning
confidence: 99%
“…Within the reviewed studies, the involvement of the local community has been identified as a key factor for building legitimacy within the community and for being able to mobilise the necessary resources that support the emergence and the sustainability of these organisations (Healey, 2015;Jarl Borch et al, 2008;Valchovska and Watts, 2016;Vestrum, 2014;Vestrum et al, 2017). This local involvement also shows the critical role played by volunteers' time, energy and expertise, both in the emergence and sustainability of rural social enterprises (Calderwood and Davies, 2012;Farmer et al, 2008;Haugh, 2007;Ludvig et al, 2018;Perry and Alcock, 2010). Nevertheless, the presence of volunteers also carries downsides, as they can limit the growth potential of the organisations, create tension with paid staff and an excessive reliance on them can provoke volunteer fatigue and burn-out (Calderwood, 2013;Sonnino and Griggs-Trevarthen, 2013;Wyper et al, 2016).…”
Section: Social Enterprises In Rural Areasmentioning
confidence: 99%
“…In forestry, mutual arrangements and collective action, for example community forestry [26] can result in institutional changes also taking the form of altered actors' arrangements [27]. The inclusion of civil society leads to institutional change that tends to lead to the re-organisation of societal actors (forest owners, forest managers, consumers, producers) and their relationships [28].…”
Section: Theoretical Background: Social Innovation and Forest Governancementioning
confidence: 99%
“…Examples for community engagement can be found in grassroots movements that evolve through investment of a considerate amount of continuous volunteer work. Such types include community forestry activities like Coppice Wood College (CWC) or Woodlands Skills Centre (WSC) in Wales on communal woodland [39]. Their collective activities have evolved over many years and combine social forestry and communal land management with skills-based training and educational services on woodland management as well as craft-making.…”
Section: Participation and Collective Action In The Forest Bioeconomymentioning
confidence: 99%